A Comprehensive Study on Challenges and Opportunities for Enhancing Professional Education among Muslim Women - Kowsar, Heena; Naidu, R. Vijaya Krishna; Salma, Shaik Ummi; Kumar, L. Satish; Vikram, Maheswari (Journal of Neonatal Surgery, 2025)
This study focuses on the challenges Muslim women in India face when trying to pursue professional education. Despite progress in women’s education worldwide, Muslim women in India still struggle with lower percentage of professional education. An attempt has been made in this study to find out the root causes for this phenomenon and also to identify possible measures to abate it. This research combines surveys and interviews with women between 18 and 35 age group in both urban and semi-urban areas, using a set of rubrics. The results pointed out to several factors such as economic hardships, cultural norms, early marriages and demanding family expectations, to be the root causes. Meagre government support and access to scholarships, especially in rural areas where transportation and educational facilities are lacking, too contribute to the lowered professional education rates among Muslim women. To tackle these issues, there’s a need for government policy changes, better community support, and stronger educational infrastructure. On implementation of these changes, Muslim women could break free from the limitations of poverty and cultural inhibitions and gain better access to professional education, allowing them to not only improve their lives but also contribute to society as a whole. Thus, this study has explored the root causes for the low percentage of professional education among Muslim women and also suggests practical solutions for betterment of the same.